49.5k views
0 votes
Write the five term sequence that would represent each recursive rule f(x) = f(x-1) -7; f(2) = 12

User Ssynhtn
by
5.4k points

1 Answer

2 votes

Answer:

Required five terms of sequence are 19 , 12 , 5 , -2 and -9 .

Solution:

Need to find the five terms of the sequence.

Given recursive rule is f(x) = f(x-1) -7

Substituting x = 2 , f(2) = f(2-1)-7

= f(2) = f(1) – 7 ------(1)

Also given that f(2) = 12.

On substituting the given value of f(2) in eq (1) we get

12 = f(1) – 7

f(1) = 12 + 7 = 19

Using given recursive rule and given value of f(2) calculating f(3)

Substituting x = 3 ,

f(3) = f(3-1) – 7

= f(2) – 7

= 12 – 7

= 5

Using given recursive rule and calculated value of f(3) calculating f(4)

Substituting x = 4,

f(4) = f(4-1) – 7

= f(3) – 7

= 5– 7

= -2

Using given recursive rule and calculated value of f(4) calculating f(5)

Substituting x = 5,

f(5) = f(5-1) – 7

= f(4) – 7

= -2– 7

= -9

Hence required five terms of sequence are 19 , 12 , 5 , -2 and -9 .

User Bryan Dellinger
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.